Penyusunan Indeks Artikel Jurnal Beranotasi Bidang Pendidikan Tahun 2008-2012 di Perpustakaan Universitas Negeri Padang - Nst., Lenni; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of writing this paper is to describe the process of indexing journal articles annotated in education as a means of information retrieval. Data obtained from direct observation in the Library of the State University of Padang. Analyzing data descriptively. Process adopted in the preparation of an annotated index of journal articles in education are: (1) collecting journal browse journals by education in Padang State University Libraries, (2) selecting and classifying journals, (3) create a description of the article, (4) make annotations in the form of article a brief description of the contents of the document, (5) determine the key words contained in the article, (6) create an index of journal articles education; (7) compiled an annotated journal articles index education; (8) typing index. Keywords: index; articles; journal; annotation; education Â